2022
DOI: 10.1016/j.molmet.2021.101413
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Y1 receptor antagonism protects β-cells and improves glycemic control in type 2 diabetes

Abstract: Objectives Loss of functional β-cell mass is a key factor contributing to poor glycemic control in advanced type 2 diabetes (T2D). We have previously reported that the inhibition of the neuropeptide Y1 receptor improves the islet transplantation outcome in type 1 diabetes (T1D). The aim of this study was to identify the pathophysiological role of the neuropeptide Y (NPY) system in human T2D and further evaluate the therapeutic potential of using the Y1 receptor antagonist BIBO3304 to improve β-cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 49 publications
2
6
0
Order By: Relevance
“…Interestingly, while administration of GEP12 did not result in a reduction in GLP-1R internalization, when evaluated in the presence of a Y1-R antagonist, it elicited increased insulin secretion in rat islets compared to results obtained with either GEP44 or Ex-4. These findings are consistent with the reduced rates of insulin secretion observed in islets in response to agonism at Y1-R (Yang, Ann-Onda et al 2022).…”
Section: Introductionsupporting
confidence: 88%
“…Interestingly, while administration of GEP12 did not result in a reduction in GLP-1R internalization, when evaluated in the presence of a Y1-R antagonist, it elicited increased insulin secretion in rat islets compared to results obtained with either GEP44 or Ex-4. These findings are consistent with the reduced rates of insulin secretion observed in islets in response to agonism at Y1-R (Yang, Ann-Onda et al 2022).…”
Section: Introductionsupporting
confidence: 88%
“…Some of these identified genes have played a key role in understanding the working mechanism of pancreatic cells [33, 34]. In Figure S2.2 in Supplementary Additional File 2, we identified four transcription factors-SP1, HDAC1, EGR1 and E2F1.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 2 shows the highly connected subgraphs obtained from the PPI network, which include the following 16 genes: PPY, PYY, NPY, GNG12, BSG, HSP90AA1, HSPA8, RBM39, H1-2, HSP90AB1, RRM2, TUBBB, ATP5F1B, ACTB, SLC25A5, and EEF1A1. Some of these identified genes have played a key role in understanding the working mechanism of pancreatic cells [33,34]. In Figure S2.2 in Supplementary Additional File 2, we identified four transcription factors-SP1, HDAC1, EGR1 and E2F1.…”
Section: Dataset1mentioning
confidence: 99%
“…Chemokines and chemokine receptors have long been associated with obesity-linked inflammation and insulin resistance and modulation of the chemokine/Chemokine receptor axis is considered a novel approach for the treatment of obesity and associated metabolic disorders (31)(32). Similarly, previous studies have reported increased expression of NPYR1 expression in adipose tissue of obese human subjects and high-fat diet-fed mice (34)(35). Moreover, selective antagonism of pe-ripheral NPYR1 was shown to prevent insulin resistance and other metabolic abnormalities in high-fat diet-fed mice (36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…Many GPCRs in this list have previously been studied for their role in adipose biology. These include alpha-and beta-adrenergic receptors (11)(12)(13)(14)(15)(16), adenosine receptors (19), free fatty acid receptors (7,17,18), adhesion receptors (20,21), hydroxycarboxylic acid receptors (22,23), gastric inhibitory peptide (27)(28)(29), chemokine receptors (30)(31) and many others (32)(33)(34)(35). Interestingly, many GPCRs with notable expression profiles in adipose tissue and adipocytes have no known role in adipose metabolism.…”
Section: Gpcrs Of Interestmentioning
confidence: 99%